Light - Taylor, Kim. (New York : Wiley, 1992)
An introduction to light and its importance to life on Earth. Includes simple experiments for children.
Includes index.
Keywords: Light -- Experiments -- Juvenile literature; Light -- Juvenile literature; Light -- Experiments; Light; Light -- Experiments; Light